Post-Secondary Education in the Inner-City: Breaking barriers and building bridges in a divided city - MacKinnon, Shauna (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2020)
The Department of Urban and Inner-City Studies (UICS) is a department in the faculty of Arts at the University of Winnipeg in Manitoba, Canada. The Department is located outside of the main campus in one of Canada’s poorest neighbourhoods. UICS is intentionally located here to offer access to postsecondary education to people who might not otherwise attend university. Our department aims to encourage people who have come to believe that university is ‘not for them’. It also serves to bring students from other areas of the city into the neighbourhood to begin to dispel long held misconceptions about the North End. We continue to develop our critical, place-based model in the spirit of putting ‘reconciliation into action’. As described by Senator Murray Sinclair, the former Chair of the Truth and Reconciliation Commission of Canada, it is “‘up to society’ to step up and take the actions that are needed." (CBC 2017). At UICS, we are committed to ‘stepping up’ by creating opportunities for learning through honest dialogue, and challenging systemic divides in our community.